(untitled) (Revista Electrónica Calidad en la Educación Superior, 2019)
In the higher education scenario, the study plans required to strengthen the set of technical, soft and complementary skills in the student body. The research generated several results when conducting interviews (2016 and 2017) with leaders of companies that operate their business in information and communication technology (ICT) in Costa Rica. From the perspective of the academic offer in the field (ICT), the curricula of the careers must have exit profiles that fit a global context, that is, of a generation of students immersed in a digital culture and in a Globalized commercial environment based on a digital economy (Tirole, 2017; Lombardeo, 2015). The problem arises to the extent that the changes made to the curricula and, specifically, to each subject, do not deepen in promoting soft and complementary skills. The main result is the analysis of skills and how to define, implement and manage them within the curriculum. Equally important, research revealed some factors that impede its optimal development. Research is the first stage that will lead us to propose a comprehensive model for the identification, selection, application and evaluation, in a systematic way, that strengthens the study plans of careers in the field of ICT.